2020
DOI: 10.1007/s10529-020-02792-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of HPV16,18,31,45 E5 and E7 peptides-based vaccines predicted by immunoinformatics tools

Abstract: Objectives Viral oncoproteins are ideal targets in therapeutic vaccines for functional inhibition of human papillomaviruses (HPVs). Herein, we designed the peptide constructs derived from E5 and E7 oncoproteins of high-risk HPV types 16, 18, 31 and 45 using the bioinformatics tools and investigated their potency in mice. Results The framework of the combined in silico/ in vivo analysis included (1) to determine physicochemical properties of the designed constructs, (2) to identify potential IFN-c-inducing epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(49 reference statements)
0
32
0
Order By: Relevance
“…and Mahmoudvand et al 44 used L1 protein to predict the epitope. In another study, Namvar et al selected the E5 and E7 proteins from HPV16/18/31/45 as target proteins for epitope prediction 45 . The E6 and E7 proteins are key targets in the development of therapeutic vaccines against cervical cancer 46 for a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…and Mahmoudvand et al 44 used L1 protein to predict the epitope. In another study, Namvar et al selected the E5 and E7 proteins from HPV16/18/31/45 as target proteins for epitope prediction 45 . The E6 and E7 proteins are key targets in the development of therapeutic vaccines against cervical cancer 46 for a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Since now we know enough information about SARS-CoV-2's genomics and proteomics, we can design peptide vaccines based on a neutralizing epitope. These immunoinformatics methods have made a significant impact on the immunology researches and we can see many examples of in silico design of epitope-based vaccines against many viruses including human immunodeficiency virus (HIV) [16], human papillomavirus (HPV) [38,39], SARS-CoV [40], rhinovirus [41]. SARS-CoV-2 is an RNA virus tending to mutate more frequently [42].…”
Section: Discussionmentioning
confidence: 99%
“…For CTL epitopes, N 103-113 , S 868-876 , M [36][37][38][39][40][41][42][43][44][45][46] , S 1094-1102 , M 102-111 , S 1051-1061 , S 360-368 , S 191-199 and S 686-696 had the highest average of interaction similarity score, respectively and For HTL epitopes, M 107-128 , N [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] , S 689-704 , S 1057-1074 , S 196-231 , N 328-349 , S , N 126-143 , M 163-181 and S 114-130 had the highest average of interaction similarity score, respectively. Overall, CTL epitopes showed better quality of docking in comparison with HTL epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…For 3D modeling of the Gag-Pol-Env-Nef-Rev and Hsp70-Gag-Pol-Env-Nef-Rev constructs, I-TASSER server was used. The C-score for evaluation of 3D structure accuracy normally is in the range of -5 to 2 and the greater value of C-score shows better quality of prediction (Namvar et al 2020). Our data indicated that the accuracy of Hsp70-Gag-Pol-Env-Nef-Rev was greater than Gag-Pol-Env-Nef-Rev, and the quality of the predicted 3D structures was improved after refinement.…”
Section: Discussionmentioning
confidence: 74%